Retrospective analysis of inpatients in a recently established palliative care center (Annals of Medical Research, 2021)
Aim: The present study makes a retrospective analysis of the records of patients admitted to a recently established district state hospital palliative care center for treatment.Material and Methods: The records of the first 252 patients treated as inpatients in a recently established palliative care center between November 2015 and April 2017 were reviewed retrospectively.Results: The study included 252 patients who were treated between the specified dates following the date of establishment. The mean age of the patients was 74 (18–103) years; 56.8% were male and 43.2% were female. The mean length of hospital stay was 15.2 days. Of the total, 134 (53.1%) patients required analgesics; 219 (86.6%) received dietician support; 73 (28.9%) received psychologist support; and 205 (81%) received physiotherapist support. Of the patients, 75.4% were discharged with full recovery, 15.4% were transferred to the intensive care unit and 9.2% died. Conclusion: Palliative care has recently gained importance as a multidisciplinary approach. The authors believe that the establishment of such centers in district hospitals will reduce overcrowding in the larger centers, and will allow patients to access this service closer to their place of residence.
Keywords: Palliative care; pain; multidisciplinary approach